1985
DOI: 10.1016/0035-9203(85)90391-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunity after treatment of human schistosomiasis mansoni. II. Identification of resistant individuals, and analysis of their immune responses

Abstract: Intensities of re-infection were monitored at three-monthly intervals after treatment of Schistosoma mansoni infections in a group of 119 Kenyan schoolchildren, whose levels of water contact were also observed. 22 children showed high reinfection intensities (greater than 100 eggs per gram of faeces) by 12 months after treatment, and were considered to be susceptible. Out of 70 children who showed low reinfection intensities during the same period (less than 30 eggs per gram), 35 showed high levels both of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(114 citation statements)
references
References 34 publications
5
106
1
2
Order By: Relevance
“…The results did not show any significant difference in the anti-SWAP IgE responses between the NE and infected patients while those treated and resistant to reinfection had a significant increase in this antibody level. The anti-IgE results with sera from treated resistant individuals are in agreement with those previously published (26)(27)(28)(29)(30)(31). The most interesting data were obtained when sera from these individuals were used in IgE antischistosomula tegumental antigen assays.…”
Section: Normal Endemic Individualssupporting
confidence: 90%
“…The results did not show any significant difference in the anti-SWAP IgE responses between the NE and infected patients while those treated and resistant to reinfection had a significant increase in this antibody level. The anti-IgE results with sera from treated resistant individuals are in agreement with those previously published (26)(27)(28)(29)(30)(31). The most interesting data were obtained when sera from these individuals were used in IgE antischistosomula tegumental antigen assays.…”
Section: Normal Endemic Individualssupporting
confidence: 90%
“…In addition to the intensity of transmission, age < 14 5 and sexual immaturity in humans have been associated with increased reinfection with S. mansoni. [6][7][8] Male sex has also been associated with increased susceptibility and severity of schistosomiasis, both in laboratory animals, 9 and population studies conducted in endemic areas. 10 To study whether other host factors, such as immune responsiveness or nutritional status, might be related to treatment outcome, we conducted a prospective cohort study of 106 infected children.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggested that human susceptibility/resistance to infection by S. mansoni was genetically determined. [2][3][4][5] To investigate whether a major gene controls human levels of infection by S. mansoni, segregation analysis of infection intensities, adjusted for water contact, age and sex was performed on 20 Brazilian pedigrees comprising 269 individuals, 6 and led to the detection of a co-dominant major gene controlling the infection by S. mansoni. The frequency of the allele predisposing to high infection levels was 0.20-0.…”
Section: Introductionmentioning
confidence: 99%